Traveling frames: How corporate and civil society actors try to influence public administration and courts in a case on nuclear emission data in Switzerland. Issue 1 (13th November 2019) - Lock, Irina; Stachel, Charlotte; Seele, Peter
Abstract : This paper focuses on the framing strategies lobbyists apply to influence public policy in a case on nuclear emission data in Switzerland. Framing analysis is at the heart of communication science and has been applied in lobbying settings, but framing theory has not yet been fine‐tuned to the specificities of public affairs research. This qualitative case study gives insights into the dominant frames seven actors ranging from corporations to nongovernmental organizations to public institutions employ to defend a legal court case in the nuclear power industry. The results of the document analysis and the interviews show that frames travel among diverse actors and only some are picked up by the courts, at times stating a position opposite to the one initially intended by the frame sponsor. A public affairs‐specific integrated process model of framing is presented that views the media in the role of a moderator in the framing process and pronounces the lobbying organizations' strategic goals, the different stakeholders as target audiences, and the outcomes of the public affairs process.